The Iron-Responsive Genome of the Chiton Acanthopleura granulata. (15th December 2020) - Varney, Rebecca M; Speiser, Daniel I; McDougall, Carmel; Degnan, Bernard M; Kocot, Kevin M
Abstract: Molluscs biomineralize structures that vary in composition, form, and function, prompting questions about the genetic mechanisms responsible for their production and the evolution of these mechanisms. Chitons (Mollusca, Polyplacophora) are a promising system for studies of biomineralization because they build a range of calcified structures including shell plates and spine- or scale-like sclerites. Chitons also harden the calcified teeth of their rasp-like radula with a coat of iron (as magnetite). Here we present the genome of the West Indian fuzzy chiton Acanthopleura granulata, the first from any aculiferan mollusc. The A. granulata genome contains homologs of many genes associated with biomineralization in conchiferan molluscs. We expected chitons to lack genes previously identified from pathways conchiferans use to make biominerals like calcite and nacre because chitons do not use these materials in their shells. Surprisingly, the A. granulata genome has homologs of many of these genes, suggesting that the ancestral mollusc may have had a more diverse biomineralization toolkit than expected. The A. granulata genome has features that may be specialized for iron biomineralization, including a higher proportion of genes regulated directly by iron than other molluscs. A. granulata also produces two isoforms of soma-like ferritin: one is regulated by iron and similar in sequence to the soma-like ferritins of other molluscs, and the other is constitutively translated and is not found in other molluscs. The A. granulata genome is a resource for future studies of molluscan evolution and biomineralization.